Effective Stress Management among Accounting Students at the Faculty of Accounting, Thonburi University - เสรีคุณาคุณ วัฒนา; กิจเจริญ มยุรี; อุ้ยศิริพร จรรยวรรณ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The objectives of this research were: 1. To study the appropriate stress level of accounting students in the Faculty of Accountancy, Thonburi University; and 2. To compare the appropriate stress management of accounting students in the Faculty of Accounting, Thonburi University classified by gender, academic level, curriculum, academic achievement, and family status. The sample consisted of 50 first- to fourth-year accounting students in the Faculty of Accountancy, Thonburi University, using stratified and simple random sampling. The research instrument was a questionnaire. The statistics used for data analysis included percentage (%), mean (x̄), standard deviation (S.D.), t-test, and one-way ANOVA. The results revealed that: 1) accounting students in the Faculty of Accountancy, Thonburi University, had a high level of appropriate stress management; 2) male and female accounting students in the Faculty of Accountancy, Thonburi University, had no difference in appropriate stress management; and 3) accounting students in the Faculty of Accountancy, Thonburi University, with different academic levels did not differ significantly. There was a statistically significant difference in appropriate stress management at the .05 level. 4) accounting students from the Faculty of Accountancy, Thonburi University, with different academic programs showed no statistically significant difference in appropriate stress management. 5) accounting students from the Faculty of Accountancy, Thonburi University, with different academic achievements showed a statistically significant difference in appropriate stress management at the .05 level. 6) accounting students from the Faculty of Accountancy, Thonburi University, with different family status showed no statistically significant difference in appropriate stress management.